Speed control of DC motor by using Pulse Width Modulation / Rosli Jahaya - Jahaya, Rosli (2005)
This paper presents a method of speed control of dc motor by constructing a full wave rectifier circuit controlled by Pulse Width Modulation (PWM) switching technique. The Insulated Gate Bipolar Transistor (IGBTs) is used as the main switching devices and the Xilinx, Field Programmable Gate Arrays (FPGAs) is used to control signal for required Pulse Width Modulation (PWM) switching pattern. The straight PWM switching technique is used to control the output voltage by changing the modulation index (ma). Thus, the speed of dc motor can be controlled by the modulation index.